Creating vascular models by postprocessing computed tomography angiography images: a guide for anatomical education. - Govsa, Figen; Ozer, Mehmet; Sirinturk, Suzan; Eraslan, Cenk; Alagoz, Ahmet (Surgical & Radiologic Anatomy, 2017)
Background: A new application of teaching anatomy includes the use of computed tomography angiography (CTA) images to create clinically relevant three-dimensional (3D) printed models. The purpose of this article is to review recent innovations on the process and the application of 3D printed models as a tool for using under and post-graduate medical education. Methods: Images of aortic arch pattern received by CTA were converted into 3D images using the Google SketchUp free software and were saved in stereolithography format. Using a 3D printer (Makerbot), a model mode polylactic acid material was printed. Results: A two-vessel left aortic arch was identified consisting of the brachiocephalic trunk and left subclavian artery. The life-like 3D models were rotated 360° in all axes in hand. Conclusions: The early adopters in education and clinical practices have embraced the medical imaging-guided 3D printed anatomical models for their ability to provide tactile feedback and a superior appreciation of visuospatial relationship between the anatomical structures. Printed vascular models are used to assist in preoperative planning, develop intraoperative guidance tools, and to teach patients surgical trainees in surgical practice.